International Cooperation in Prevention and Combating Human Trafficking in Southeast Asian Region: A Case Study of Vietnam - Huyen, Tran Quang (2020)
In recent years, Vietnam has recorded as transnational hubs among of complicate region relating human trafficking. The distinguish features of geography shared borderland with three countries, namely Cambodia, China and Laos, making cross-border trafficking in persons more dynamic and even more challenged for law enforcement agencies to prevent and combat this crime. Alongside with internal efforts to anticipate human trafficking, from 2010 to 2020, Vietnam’s government implemented officially two national programs on prevention and combating human trafficking with a number of specific projects and its related goals. Amongst, to enhance international cooperation between neighbored countries and regional and international partnerships that is considered as one of the most prioritized strategies of Vietnam. This paper focuses on analysis policies and implications of Vietnam through providing details of the current viewpoints in international cooperation to fight trafficking in human beings. Some main trends and patterns of human trafficking in Vietnam in the past years will illustrate the nature of complex situation. Then, some recommendations call for further research to ensure the effectiveness of international cooperation. Keywords: Human trafficking; crime prevention; international cooperation; Vietnam DOI: 10.7176/JLPG/94-04 Publication date: February 29th 202